1973
DOI: 10.1042/bj1350353
|View full text |Cite
|
Sign up to set email alerts
|

The catalase activity of ferrihaems

Abstract: 1. The variation of the specific stoicheiometric catalatic activity of proto- and deuteroferrihaem with total ferrihaem concentration has been studied at 25 degrees C over a wide range of pH. For deuteroferrihaem the results imply that only monomeric ferrihaem species contribute significantly to the catalatic activity. Protoferrihaem is more highly dimerized in solution and, in this system, contributions to the catalatic activity from both monomeric and dimeric ferrihaem species were observed. The ratio of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 15 publications
(14 reference statements)
5
43
0
Order By: Relevance
“…Whereas this enzyme is instrumental in protecting the cell during exposure to atmospheric oxygen and from macrophage-derived oxidants [31,32], it is likely that superoxide dismutase is an essential pre-requisite for haem acquisition from oxyhaemoglobin. Any H # O # generated by P. gingi alis through O − # dismutation would be destroyed by both monomeric and µ-oxo dimeric Fe(III)PPIX molecules by virtue of their inherent catalase activities [33].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas this enzyme is instrumental in protecting the cell during exposure to atmospheric oxygen and from macrophage-derived oxidants [31,32], it is likely that superoxide dismutase is an essential pre-requisite for haem acquisition from oxyhaemoglobin. Any H # O # generated by P. gingi alis through O − # dismutation would be destroyed by both monomeric and µ-oxo dimeric Fe(III)PPIX molecules by virtue of their inherent catalase activities [33].…”
Section: Discussionmentioning
confidence: 99%
“…We have suggested that this protein may serve as a receptor for uptake of iron(III) protoporphyrin IX. Alternatively, it may facilitate cell-surface deposition of ferrihaems which can then act defensively against attack by hydrogen peroxide by virtue of their inherent catalase activity (Brown et al, 1970;Jones et al, 1973) as recently demonstrated for Porphyromonas gingivalis (Smalley et al, 2000). However, we have found that the ability of cells to bind iron(III) protoporphyrin IX is not restricted to HBP-positive genomovar IIIa isolates (Smalley et al, 2001).…”
Section: Introductionmentioning
confidence: 39%
“…In addition, the catalase activities of cells of both genomovar IIIa and I strains after exposure to iron(III) protoporphyrin IX monomers were double those of cells carrying bound m-oxo oligomers. This finding is predictable on the basis that the catalase activity of the monomer is higher than the m-oxo oligomer (Jones et al, 1973;Brown et al, 1970). The increased catalase activity displayed by the genomovar IIIa isolates as a result of binding of ferrihaems would provide an advantage over other genomovars to endure fluxes of H 2 O 2 released from neutrophils.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations